9514 1404 393
Answer:
Explanation:
Apparently, you are supposed to assume that ...
y = g(x)
y = 4 - x
For the one given value of x, the corresponding y value is ...
y = 4 - 3 = 1
So, for that x-value, the table entry is (x, y) = (3, 1).
__
To find the missing x-values, you can solve the equation for x.
y = 4 - x
x + y = 4 . . . . add x
x = 4 - y . . . . subtract y
Now, for the given y-values, we can find the corresponding x:
x = 4 -(-1) = 5 ⇒ (x, y) = (5, -1)
x = 4 -(4) = 0 ⇒ (x, y) = (0, 4)
So, your table will be ...